STUDY OF GREEN SOLID STATE LASERS BASED ON MGO:PPLN CRYSTALS FOR LASER DISPLAY APPLICATIONS - Gan, Yi (My University, 2013)
Laser-based displays have been under active development over the past 50 years. Visible lasers are considered as the “ultimate” light sources for display applications due to their high brightness, high directionality and high color saturation. Unlike commercially available red and blue laser diodes, semiconductor laser diodes that can directly emit green light with sufficient power and efficiency required in laser display are still not ready yet. Significant effort has been paid around the world to overcome this “green bottleneck”.
The aim of this thesis is to investigate a practical solution to build a compact green laser to satisfy the cost/performance requirement for laser display applications. Frequency doubling based on MgO doped periodically poled lithium niobate (MgO:PPLN) is the main research direction of this thesis work.
The thesis focuses on several engineering issues, mainly related to practical applications. Two different approaches have been explored: single-pass frequency doubling and intra-cavity frequency doubling. In the single-pass configuration, an all-fiber Q-switched fiber laser was used as the fundamental laser source because the high peak pump power can increase the conversion efficiency. 3.1%/W/cm nonlinear conversion efficiency was achieved which show good agreements with the theoretical simulations. The single-pass frequency doubling of a novel annealing proton exchanged (APE) MgO:PPLN ridge waveguide was also investigated. Over 120 mW green laser with a 53.2% conversion efficiency was achieved. The results have shown remarkable improvements comparing with the reported waveguide devices.
On the other hand, in the intra-cavity frequency doubling, Nd:YVO4/MgO:PPLN microchips for low power (300 mW CW green power and 530 mW modulated green power) applications have been demonstrated experimentally and investigated theoretically. It has been shown that although the plane-parallel cavity structure with discrete components can provide 2.9 W green laser with 29.6% conversion efficiency, it is complex for mass production. One of the important research achievements of this thesis is to study and optimization of a novel monolithically integrated Nd:YVO4/MgO:PPLN module (namely mGreen module) which combines the advantages of the microchip structure and the discrete plane-parallel cavity structure. 1.28 Watt output green laser has been achieved through a compact configuration based on the optimized mGreen module. Power scaling based on this monolithic green laser module by employing an array concept has also been investigated. The dependence of output power on pump beam gap has been studied both theoretically and experimentally.
Keywords: Nonlinear Optics; Lasers; Second Harmonic Generation; Laser Display; Other Engineering; Other Engineering